Pengaruh Konsep Pelayanan Terhadap Keputusan Pembelian dan Tingkat Pendapatan Pada Masa Sebelum, Awal dan New Normal Pandemi (Studi Komparasi Pada Café-Café di Minggir Yogyakarta) - Susilawati, Rini (Kajian Ekonomi dan Bisnis, 2020)
The emergence of a wave of the Covid-19 pandemic that started in Indochina which eventually hit Indonesia also hit the business world on all fronts. The thing to be grateful for is the resilience of the MSME sector which is relatively able to withstand all conditions even in unexpected conditions such as Covid-19. This study uses a comparative method, namely: before the pandemic, the beginning of the pandemic (1-3 months), and during the new normal era with the object of a cafe cafe in Minggir, Sleman, Yogyakarta. From about 10 cafes in Minggir, only 5 cafes that meet the requirements were selected as research samples. By using SPSS analysis it is known that for the period before the pandemic the following regression results were obtained: Service concept = 0.819 + 0.805 (purchase decision) +0.391 (income level), at the beginning of the pandemic: Service Concept = 0.819 = 1.470 (Purchase Decision) + 36.1 ( Income Level), and in the New Normal era: Service Concept = 6,273 + 0.364 (Purchase Kep) +19.55 (Income Level). So it is found that there is a significant difference between cafe managers who use online services and social media and those who are vacuum (without social media activity) to establish communication with customers. The impact was very real even in the New Normal era. In conclusion, cafe managers who used social media in the early days of the pandemic, in fact in the new normal era, the level of purchase and income increased by 50%, it is assumed that from the additional new customers obtained at the beginning of the pandemic due to the influence of social media.